(3GdEYLGR aj GdbQBfs - (3GdHUQj, GdbGVj, GdeJcde, GdCTYQj, GdHGbdGfj, CHh HcQ GdHGbdGfj, eMeO Hf GdWjH Hf eMeO Hf LYaQ Hf GdbGSe (B403(3g`s ((3GdTQja MSf GHf GdTQja eMeO GHf GdTQja Ydj GHf GdTQja MSjf GdSeQbfOjs)
(3BNQgG (B:s
(3YdjgG UhQ SeGYGJ YOI efbhdI ef GdCUd GdPj fbdJ Yfg, hSeGY BNQ UMjM YdjgG gj HNW(B: (3jhSa Hf Ndjd Hf YHO Gddg GdOeTbjs
(3eUOQ GbJfGA GdCUd (B:s
(3aGVd CMeOs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3YdjgG Jedc d`(B: (3eMeO Hf YHO GdbGOQ Hf gHI Gddgs
Keywords: (3GdJaSjQ hYdhe GdbQBfs